2016
DOI: 10.1007/s00213-016-4348-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular serum signature of treatment resistant depression

Abstract: Overall, our findings suggest that proteins, which are involved in immune and complement activation, may represent potential biomarkers that could be used by clinicians to identify high-risk patients. Nevertheless, given that the molecular changes between the staging groups were subtle, the results need to be interpreted cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…However, increase in pro-inflammatory cytokines and other inflammatory factors in plasma/serum from patients with depression have been reported in several studies ( Dowlati et al, 2010 ; Dahl et al, 2014 ). Plasma and serum proteomic studies of patients with major depressive disorders have found altered levels of acute phase, complement, and metabolic proteins similar to our study ( Lee et al, 2015 ; Ruland et al, 2016 ). These studies indicate that changed anxiety or depression status could affect proteins systemically.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, increase in pro-inflammatory cytokines and other inflammatory factors in plasma/serum from patients with depression have been reported in several studies ( Dowlati et al, 2010 ; Dahl et al, 2014 ). Plasma and serum proteomic studies of patients with major depressive disorders have found altered levels of acute phase, complement, and metabolic proteins similar to our study ( Lee et al, 2015 ; Ruland et al, 2016 ). These studies indicate that changed anxiety or depression status could affect proteins systemically.…”
Section: Discussionsupporting
confidence: 88%
“…As mentioned above, psychological distress is common in CWP and is often measured using the Hospital Anxiety and Depression Scale (HADS) ( Zigmond and Snaith, 1983 ). Because the association between depression and several serum proteins has been shown in patients with major depression disorder, ( Lee et al, 2015 ; Ruland et al, 2016 ) it is important to investigate whether the protein pattern in blood correlates with psychological distress in CWP patients and to what extent these proteins influence pain intensity. The same principal reasoning goes for Body Mass Index (BMI) since increased BMI is often found in patients with CWP/FMS ( Neumann et al, 2008 ) and the correlation between limited numbers of plasma/serum metabolites and proteins and BMI have been reported ( Xiao et al, 2013 ; Rus et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although, there were no significant differences in weight or BMI in this cohort, it is generally known that one of the risk factors is obesity in females with CWP/FMS 44,45. Several studies have also found a correlation between higher levels of CERU, haptoglobin and complement proteins in plasma and serum to be associated with major depressive disorders 4650. In this study, the CWP group reported statistically significant higher HADS scores (anxiety and depression) compared to CON.…”
Section: Discussionmentioning
confidence: 56%
“…Most of these proteins are related to the innate immune response, inflammation and the coagulation cascade. Effects on protein components of these pathways have been reported previously for MDD patients at risk of suicide (Yang et al, 2016 ) and as markers of treatment resistance (Ruland et al, 2016 ). Furthermore, in a previous study, we found that levels of fibrinogen, a key component of the clotting cascade, may be predictive of antidepressant treatment response (Martins-de-Souza et al, 2014 ).…”
Section: Resultsmentioning
confidence: 68%
“…In addition, three proteins associated with a transport function were lower including apolipoprotein A-IV, apolipoprotein B-100 and retinol-binding protein 4. Previous studies have identified lower levels of all of these proteins in major depression patients (Lopez-Vilchez et al, 2014 ; Frye et al, 2015 ; Lee et al, 2016 ; Ruland et al, 2016 ; Kim et al, 2017 ). In addition, the finding of lower levels of apolipoprotein A-IV in responders is consistent with the findings of a recent study showing that this protein may be a marker of response to different antidepressants (Ruland et al, 2016 ).…”
Section: Resultsmentioning
confidence: 94%